A transformação digital no Tribunal de Justiça do Estado de São Paulo: o caso da 4ª Vara Cível da Comarca de Bauru - Fiorini, Juliana de Camargo (2024)
This research aims to investigate the digital transformation in the Court of Justice of the State of São Paulo, specifically in the 4th Civil Court of the District of Bauru. To this end, a historical contextualization of the digital transformation process is carried out, and an analysis of the dimensions of the digital transformation process and the benefits found in the light of scientific literature. Subsequently, the process of digital transformation in the public sector and specifically in the Brazilian Judiciary is covered in depth, analyzing the transformations resulting from the implementation of the electronic judicial process as one of the tools used in order to adapt the way of working to the technological innovations resulting from the evolution of information and communication technologies. The implementation challenges and benefits found with digital transformation in the public sector are also analyzed. The methodological path follows the precepts of qualitative research, uses the single case study method and collects data through documentary research, semi-structured interview scripts and participant observation. A single case study is carried out in the 4th Civil Court of the District of Bauru, in order to verify the challenges faced by civil servants when implementing the electronic judicial process in each of the dimensions of the digital transformation process and whether the benefits found in the literature were felt in that judicial unit of the Court of Justice of the State of São Paulo. In this way, the following were carried out: (i) documentary research on the website of the organization studied, in search of regulations that regulate digital transformation, (ii) interviews with 66.6% of employees - technicians and magistrates - of the 4th Civil Court of the District of Bauru, belonging to the Court of Justice of the State of São Paulo to understand the digital transformation process in that unit, through the analysis of each of the dimensions proposed in the literature and the benefits felt or not by employees with the use of the electronic judicial process , and (iii) participant observation to discuss the challenges and benefits experienced with the digital transformation in that judicial unit. The results indicated that the 4th Civil Court of Bauru developed in the human-technological and organizational dimensions, while there was partial development in the human and technological dimensions. It is also concluded that in the organizational-technological and organizational-human dimensions there was no satisfactory development. In relation to benefits, it was found that the levels of delivery of results (efficiency), quality of service and productivity were met, while only the level of meeting citizen expectations only partially reached the expected level. Finally, an analysis model for digital transformation at the Court of Justice of the State of São Paulo is presented, which can be replicated in other organizations, public or private.